Perillaldehyde reduces mitochondrial oxidative stress damage by regulating KCNT2/NR1D1 protein activity in vascular dementia rats - Qian-qian Wang; Hong-dou Zhang; Pei-yao Liu; Chun-rui Zhang; Bao-yue Cui; Xi-yue Li; Meng-yao zhao; Jin-he Yang; Peng Li; Ya-ling Yin; Xue-yu Sun (Molecular Biology Reports, 2026)

Planarization engineering of benzodithiophene-based nanogrids for enhanced carrier mobility and emission performance - Lei Yang; Jun Yang; Shi-rui Chen; Wen-bin Xie; Cong Sun; Wang-yang Wu; Xin-zhe Peng; Manas Ranjan Dash; Xue-qin Ran; Mohamad Akbar Ali; Ling-hai Xie (Chemical Engineering Journal, 2026)

Iterative precursor rebalancing improves phenazine-1-carboxylic acid production in engineered Pseudomonas chlororaphis - Sheng-Jie Yue; Peng Huang; Chen Song; Song Li; Rui Lian Yao; Wei Wang; Xue-Hong Zhang; Pablo I. Nikel; Hong-Bo Hu (Bioresource Technology, 2026)

A pH-responsive sequential-releasing hydrogel breaks the infection-inflammation-oxidative stress cycle to promote vascularized healing in refractory anal fistula - Qiuqun Xiao; Kailan Liu; Manzhen Zhou; Ruyi Peng; Luyang Dai; Rui Zhang; Lin Luo; Yong Xue; Yunrui Hu (Chemical Engineering Journal, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Initial exploration of the health effects on Qinghai-Tibetan Plateau yaks following short-term exposure to polystyrene microplastics: Analysis of rumen microbiota, host metabolism, antioxidant function and inflammatory responses - Penghu Zhang; Yanbing Zhu; Zhisheng Wang; Peiqiang Yu; Bai Xue; Lizhi Wang; Rui Hu; Huawei Zou; Yahui Jiang; Jianxing Xiao; Cui Tan; Fali Wu; et al. (Journal of Hazardous Materials, 2026)

Development of a triplex RT-qPCR assay for rapid and accurate detection of porcine rotavirus, porcine epidemic diarrhea virus, and porcine deltacoronavirus - Yuhan Yang; Xingyu Xiao; Meixuan Ren; Ningning Jiang; Xiaoxu Xie; Xue Zheng; Rui Yin; Shiyu Luan; Jingnan Wang; Peng Li (Veterinary Research Communications, 2026)

A machine learning approach coupling immediate and lagged drivers to predict sand and dust storms in Northern China - Mile Wang; Kunxia Yu; Peng Li; Zhanbin Li; Rui Yan; Zixia Jiang; Xue Li; Lu Jia (Journal of Environmental Management, 2026)

Triterpenoids in the leaves of Schisandra chinensis (Turcz.) Baill. treated AD by inducing mitophagy through activation of MCL-1 - Shi-Qi Xu; Xin Meng; Xu Yang; Gang-Tao Bu; Si-Yi Wang; Meng-Meng Li; Yi-Qiang Zhang; Zhi-Chao Hao; Wei Guan; Qi-Shan Chen; Li-Li Zhang; Rui-Yan Wu; et al. (Food Bioscience, 2026)

Three-Dimensional Fast Marching Seismic Traveltime Computation Based on Coarse-Grid Interpolation - Yan-song Li; Jun-jie Yang; Xue-feng Gao; Hui Sun; Yun Long; Peng Lin; Song-da Ji; Hong-yong Ren; Rui Chen (Applied Geophysics, 2026)

Deciphering the mechanisms underlying cadmium tolerance in the endophytic fungus Trichoderma atroviride D16 - Xue-Wen Bi; Xing-Guang Xie; Wen-Jing Zhang; Rui-Di Zhang; Khalid Rahman; Xin-Zhu Yu; Cun-Yu Fan; Shu-Lang Ding; Yu-Qing Peng; Ting Han (Fungal Biology, 2026)

Multiplex PCR and nanopore sequencing reveal the genetic stability of Hantaan virus in Xi’an, China - Hailong Chen; Peng Zhang; Xiaoyue Chu; Yangni Deng; Mengying Yu; Leile Zhang; Quanli Du; Yuewen Han; Yujie Yang; Zerun Xue; Shuling Li; Rui Wu; et al. (Archives of Virology, 2026)

Tracking the eyes to track decline: Global eye movement similarity as a novel neuropsychological marker of mild cognitive impairment - Zhan Wang; Hong-Zhou Xu; Fang Fang; Xue-Rui Peng; Ying-Chen Liu; Zhi-Jun Zhan; Jing Yu (GeroScience, 2026)

Estrogen inhibits granulosa cell apoptosis via nuclear receptors by suppressing death receptor and mitochondrial pathways in goat small antral follicles - Sihai Lu; Baijuan Yue; Yaju Tang; Haoyu Xu; Rui Xu; Xiaoe Zhao; Qiang Wei; Jia Xue; Meng-Hao Pan; Sha Peng; Baohua Ma (Theriogenology, 2026)

Corrigendum to “Construction of covalent organic framework electrospun composite nanofiber membranes for the efficient extraction and detection of phenylurea herbicides” [Food Chem. 496(Part 2) (2025) 146787] - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Hong Wang; Hong-Tao Lei; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2026)

Efficient bioconversion of corn stover hydrolysates into phenazine-1-carboxylic acid by engineered Pseudomonas chlororaphis for sustainable biopesticide production - Sheng-Jie Yue; Yu-Xuan Li; Kai-Quan Liu; Sheng-Xiao Zhang; Peng Huang; Wei Wang; Xue-Hong Zhang; Xiang-Rui Hao; Lian Jiang; Hong-Bo Hu (Bioresource Technology, 2026)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Construction of covalent organic framework electrospun composite nanofiber membranes for the efficient extraction and detection of phenylurea herbicides - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Hong Wang; Hong-Tao Lei; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2025)

Simulation on the propagation characteristics of TEM pseudo-wavefield - Jun-jie Xue; Ke-rui Fan; Xin Wu; Zhi-peng Qi; Wen-han Li; Jiang-wei Cui (Applied Geophysics, 2025)

Hydrodynamic characteristics of horizontal-axis tidal turbine with Gurney Flap and vortex generators - Yonghui Liu; Yuqi Liu; Yu Xue; Junzhe Tan; Peng Yuan; Xiancai Si; Zhen Pei; Rui Shu; Xiaodong Liu (Ocean Engineering, 2025)

Multifunctional fluorescent sensors N/CDs@Eu-MOFs for rapid detection of childhood obesity and acute myeloid leukemia biomarkers and identification of chiral enantiomers of lysine - Liping Peng; Rui Xue; Henglong Ren; Borong Ren; Mingyue Wang; Xiuli Niu; Hao Guo; Wu Yang (Analytica Chimica Acta, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

In/S co-decorated SnSe encapsulated in a dual carbon layer for sodium ion storage - Ya Ru Pei; Yong Jin Xia; Lei Ming Wang; Rui Li; Jun Xi Peng; Xue Jing Yang; Jian Li; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2025)

Multifunctional Janus hydrogel targeting mitochondrial regulation and inflammatory pathways promotes infected burn wound repair - Xiaohui Li; Longbao Feng; Honglin Wu; Hao Yang; Peng Wang; Yongfei Chen; Yuxi Zhou; Jiayuan Zhu; Wei Xue; Rui Guo; Zhicheng Hu (Chemical Engineering Journal, 2025)

A novel bioreactor developed for the intensification of high-viscosity aerobic fermentation processes - Qian Chen; Kai Hu; Quanfei Li; Kai Yang; Chao Zhang; Weiwei Huang; Yibin Qiu; Yian Gu; Liang Sun; Peng Lei; Jian Xue; Sha Li; et al. (Chemical Engineering Journal, 2025)

Mangiferin promotes porcine oocyte maturation and delays the postovulatory aging process by up-regulating NRF2 levels - Xiuwen Yuan; Hewei Ji; Yuhao Zhang; Huilin Peng; Neng-hao Cao; Jia-jun Ren; Xue-rui Yao; Xingwei Liang; Nam-hyung Kim; Yong-nan Xu; Ying-hua Li (Theriogenology, 2025)

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Root exudates drive root avoidance of maize in response to neighboring wheat - Xiao-Tong Yin; Fang-Fang Zhang; Rui-Peng Yu; Na Liu; Wei-Ping Zhang; Dario Fornara; Liesje Mommer; Xue-Xian Li; Long Li (Plant and Soil, 2025)

LncRNA OLMALINC promotes osteosarcoma progression through USP1-mediated autophagy suppression - Jianping Li; Bo Yu; Zhaowen Xue; Yiping Liang; Shanchuang Chen; Tao Gui; Zitao Liu; Lei Zhang; Rui Peng (Human Cell, 2025)

High-throughput screening method for glycolipids based on substrate modification and their efficient biomanufacturing - Yuanyi Li; Zhilin Liu; Yiming Zheng; Ke Sun; Peng Lei; Yian Gu; Yongting Song; Jian Xue; Weidong Cai; Rui Wang; Hong Xu; Liang Sun (Bioresource Technology, 2025)

Microrna363-5p targets thrombospondin3 to regulate pathological cardiac remodeling - Yu-kun Ma; Xin-yi Han; Shu-huai Zan; Hui-ting Liu; Xue-yan Zhou; Dan-xue Zhao; Rui Xing; Peng Zhao (Molecular and Cellular Biochemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Enhanced electrochemical performance of NCM811-based batteries by using a multifunctional electrolyte additive - Aijia Wei; Shuxing Mei; Jinping Mu; Peng Liu; Xue Bai; Rui He; Xiaohui Li; Yuxin Niu; Lihui Zhang; Zhenfa Liu; Lei Wang (Chemical Engineering Journal, 2025)

Study on the evolution of ecological flow in river and its guarantee degree during different hydrological periods - Xue Chen; Qin Li; Zhuo Jia; Rui Xiao; Zhijin Cheng; Yuhao Peng (Journal of Cleaner Production, 2025)

Programmable allosteric DNA nanomachine for ratiometric imaging of VEGF in tumor cells - Jia-Wei Liang; Yan-Mei Lei; Zhao-Peng Chen; Xue-Mei Zhou; Ya-Qin Chai; Ruo Yuan; Rui Du; Ying Zhuo (Chemical Engineering Journal, 2025)

Visible light-powered photodynamic antibacterial chlorophyllin-derived metallochlorins - Yuling Xue; Kuoran Xing; Max Jing Rui Tham; Bang Lin Li; Narattam Sikdar; Lai Peng Leong; Ching Hua Lee; Justin Jang Hann Chu; Wee Han Ang; David Tai Leong (Chemical Engineering Journal, 2025)

Monthly Runoff forecasting using A Climate‑driven Model Based on Two-stage Decomposition and Optimized Support Vector Regression - Zhuo Jia; Yuhao Peng; Qin Li; Rui Xiao; Xue Chen; Zhijin Cheng (Water Resources Management, 2024)

Applications of electrospun nanofibers in food safety and quality analysis: A review - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Lin Luo; Zhen-Lin Xu (Trends in Food Science & Technology, 2024)

Corrigendum to “Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L.” [Phytochem. Lett. 55 2023, 61–66] - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2024)

Effect of anaerobic duration on nitrogen and phosphorus removal and carbon source utilization in integrated denitrifying phosphorus removal and partial denitrification coupled with anammox system - Yunlong Su; Xiyao Li; Jiao Wang; Rui Du; Xiaofei Xue; Yanwei Shi; Yongzhen Peng (Journal of Cleaner Production, 2024)

Decontamination promotes the release of incorporated organic contaminants in hair: Novel insights into non-invasive biomonitoring - Rui-Xin Qin; Xue Cao; Shi-Yi Zhang; Hong Li; Bin Tang; Qi-Long Liao; Feng-Shan Cai; Xian-Zhi Peng; Jing Zheng (Environmental Pollution, 2024)

MARCH1 and MARCH2 inhibit pseudorabies virus replication by trapping the viral cell-to-cell fusion complex in trans-Golgi network - Rui Huang; Cui-Hong Rao; Yuan-Zhe Bai; Changqing Yu; Meng Chen; Jin-Mei Peng; Shi-Jia Xu; Yue Sun; Meng Fandan; Chuang Lyu; Mirwaise Khan; Tong-Qing An; et al. (Veterinary Microbiology, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Wogonin preconditioning of MSCs improved their therapeutic efficiency for colitis through promoting glycolysis - Mengye Wu; Cuiping Li; Xue Zhou; Zhiyong Wu; Jianqi Feng; Xiaolu Guo; Rui Fang; Qinghai Lian; Ming Pan; Xiaorong Lai; Yanwen Peng (Inflammopharmacology, 2024)

Impact of remaining roots on soil nematode communities in an aboveground plant functional group removal experiment - Yong Zheng; Ligai Huang; Xue Jiang; Rui Guo; Wenjie Wan; Luping Ye; Tibor A. Drost; Xianhui Zhou; Hui Guo; Juan Zuo; Peng Wang (Plant and Soil, 2024)

Parameter sensitivity analysis of SWMM: a case study of airport airfield area - Jing Peng; Hucheng Zhao; Rui Li; Runzhao Xue (Natural Hazards, 2024)

Phenolic components from the fruits of Solanum xanthocarpum with anti-inflammatory activity - Yan Liu; Rui Yang; Hai-Dan Zou; Zhen-Peng Xu; Juan Pan; Jia-Tong Wu; Wei Guan; Zhi-Chao Hao; Adnan Mohammed Algradi; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2024)

Salvirrane A-F, six undescribed nordrimane sesquiterpene derivatives from Salvia castanea Diels f. tomentosa Stib and their cytotoxic activities - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Peng-Xue Ji; Xin-Min Li; Zi-Feng Guo; Jue Wang; Jing-Ming Jia; An-Hua Wang (Phytochemistry, 2024)

TRPML1 contributes to antimony-induced nephrotoxicity by initiating ferroptosis via chaperone-mediated autophagy - Lei Liu; Chao Luo; Dongnan Zheng; Xuehai Wang; Rui Wang; Wenjie Ding; Zhaoping Shen; Peng Xue; Shali Yu; Yifei Liu; Xinyuan Zhao (Food and Chemical Toxicology, 2024)

Effect of ambient high-temperature on real driving emission tests of a light-duty gasoline vehicle - Rui Wang; Li Zhang; Jingde Peng; Jinlin Han; Baocheng Du; Baoli Gong; Haoyang Xue; Dajiang Tuo; Qing Zhang (Atmospheric Pollution Research, 2024)

Fluid-rock interaction modeling to constrain Au enrichment: Implication for the giant Jiaodong Au mineralization, eastern North China Craton - Huan-Long Hu; Hong-Rui Fan; Ting-Guang Lan; Xue-Feng Yu; Da-Peng Li; Kui-Feng Yang (Gondwana Research, 2024)

Neuroprotective α-pyrones from Nigrospora oryzae, an endophytic fungus residing in Taxus chinensis var. mairei - Zi Yun Fan; Jing Peng; Jun Qiao Lou; Yong Chen; Xue Ming Wu; Rui Tan; Ren Xiang Tan (Phytochemistry, 2023)

Successful start-up of a novel integrated denitrifying phosphorus removal and partial denitrification coupled with anammox process for simultaneous nitrogen and phosphorus removal with fully ordinary suspended sludge - Yunlong Su; Rui Du; Jiao Wang; Junfei Qiao; Xiyao Li; Xiaofei Xue; Zhiqi Cao; Yongzhen Peng (Chemical Engineering Journal, 2023)

Phosphoproteomic Analysis Reveals the Predominating Cellular Processes and the Involved Key Phosphoproteins Essential for the Proliferation of Toxoplasma gondii - Xin-zhu Chen; Rui-xue Bai; Fei-yu Qin; Hong-juan Peng; Jin-feng Ren; Lang Hu; Yu-di Li; Cheng He (Acta Parasitologica, 2023)

Ferrostatin-1-loaded thermosensitive nanodelivery system for noise-induced hearing loss treatment - Peng-Wei Ma; Pei-Heng Lu; Hao Yuan; Jia-Wei Chen; Wei Gao; Yu-Qiang Lun; Jia-Ning Guo; Xue-Rui Ding; Rui Liang; Si-Yu Li; Zi Wang; Wei-Long Wang; et al. (Chemical Engineering Journal, 2023)

Pilot-scale demonstration of self-enrichment of anammox bacteria in a two-stage nitrification-denitrification suspended sludge system treating municipal wastewater under extremely low nitrogen loading rate - Yunlong Su; Rui Du; Jiao Wang; Xiyao Li; Qiong Zhang; Xiaofei Xue; Yongzhen Peng (Bioresource Technology, 2023)

High-performance Cu/Mn modified ceramsite as a persulfate activator to degrade oxytetracycline in batch Erlenmeyer flask and continuous-flow fixed-bed column systems: An exploration of its practicability and non-radical mechanisms - Huang-gen Yang; Mang Lu; Xue-jiao Wu; Rui-ting Dong; Tao-peng Luo; Hui-hua Zhong (Chemosphere, 2023)

Characterization of different grades of Jiuqu hongmei tea based on flavor profiles using HS-SPME-GC-MS combined with E-nose and E-tongue - Qi Peng; Shanshan Li; Huajun Zheng; Kai Meng; Xi Jiang; Rui Shen; Jingrun Xue; Guangfa Xie (Food Research International, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Maternal 25(OH)D attenuates the relationship between ambient air pollution during pregnancy and fetal hyperinsulinism - Peng Wang; Wan-jun Yin; Ying Zhang; Xiao-min Jiang; Xiao-guang Yin; Yu-bo Ma; Fang-biao Tao; Rui-xue Tao; Peng Zhu (Chemosphere, 2023)

Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L. - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2023)

Can shallow-incorporated organic mulching replace plastic film mulching for irrigated maize production systems in arid environments? - Ze-Ying Zhao; Peng-Yang Wang; Xiao-Bin Xiong; Rui Zhou; Ying Zhu; Yi-Bo Wang; Ning Wang; Kiprotich Wesly; Wei Xue; Jing Cao; Jin-Lin Zhang; Hong-Yan Tao; et al. (Field Crops Research, 2023)

TEAD4 predicts poor prognosis and transcriptionally targets PLAGL2 in serous ovarian cancer - Xin Tong; Yi-Si Liu; Rui Tong; Wei-Wei Tang; Xue-Mei Li; Chun-Yan Wang; Yong-Peng Wang (Human Cell, 2023)

Molecular characterization of a teleost-specific toll-like receptor 22 (tlr22) gene from yellow catfish (Pelteobagrus fulvidraco) and its transcriptional change in response to poly I:C and Aeromonas hydrophila stimuli - Xiu-Ying Wei; Jun Wang; Sheng-Tao Guo; Yun-Yun Lv; Yan-Ping Li; Chuan-Jie Qin; Yuan-Chao Zou; Qing-Chao Shi; Peng Hu; Xiao-Qin Xiong; Yang He; Rui Li; et al. (Fish & Shellfish Immunology, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Rapid enrichment of anammox bacteria and transformation to partial denitrification/anammox with nitrification/denitrification sludge - Yunlong Su; Yongzhen Peng; Jiao Wang; Qiong Zhang; Xiyao Li; Shuying Wang; Xiaofei Xue; Rui Du (Science of The Total Environment, 2023)

Rapid, selective, and room temperature dissolution of crystalline xylan by a hydrotrope - Qiaoling Liu; Rui Tian; Ziwen Lv; Yuying Wu; Baozhong Lv; Xiang Hao; Zhimin Xue; Feng Peng (Carbohydrate Polymers, 2023)

Plant-associated Microbe System in Treatment of Heavy Metals–contaminated Soil: Mechanisms and Applications - Zhiming Ren; Rui Cheng; Peng Chen; Yuanyuan Xue; Hong Xu; Yao Yin; Guangtuan Huang; Wei Zhang; Lehua Zhang (Water, Air, & Soil Pollution, 2023)

Acetylsalicylic acid (ASA) suppressed Fusarium rot development and neosolaniol (NEO) accumulation by activating phenylpropane metabolism in muskmelon fruit - Lan Li; Qili Liu; Huali Xue; Yang Bi; Hussain Raza; Rui Zhang; Jimdjio Kouasseu Carelle; Hui Peng; Haitao Long; Dov Prusky (European Journal of Plant Pathology, 2022)

Development and perspectives of rapid detection technology in food and environment - Xue-Xia Jia; Shuang Li; Dian-Peng Han; Rui-peng Chen; Zi-Yi Yao; Bao-an Ning; Zhi-Xian Gao; Zhen-Chuan Fan (Critical Reviews in Food Science and Nutrition, 2022)

Extracellular vesicles derived from human Sertoli cells: characterizations, proteomic analysis, and miRNA profiling - Xiao-Hui Tan; Sheng-Ji Gu; Wen-Jie Tian; Wen-Peng Song; Yang-Yang Gu; Yi-Ming Yuan; Xue-Song Li; Zhong-Cheng Xin; Sae Woong Kim; Rui-Li Guan; Woong Jin Bae (Molecular Biology Reports, 2022)

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Effects of different energy diets on DNA methylation and mRNA expression in follicle stimulating hormone receptor gene promoter region of Duolang sheep during estrus - Bo Liu; Hongjian Li; Weikun Tao; Fei Huang; Xue Rui; Jie Wang; Peng Niu; Di Fang; Qinghua Gao (Molecular Biology Reports, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Genetic diversity and population structure of Tibetan sheep breeds determined by whole genome resequencing - Lei-Lei Li; Shi-Ke Ma; Wei Peng; You-Gui Fang; Hai-Rui Duo; Hong-Yun Fu; Gong-Xue Jia (Tropical Animal Health and Production, 2021)

Advances in research of the mid-deep South China Sea circulation - Dongxiao Wang; Qiang Wang; Shuqun Cai; Xiaodong Shang; Shiqiu Peng; Yeqiang Shu; Jingen Xiao; Xiaohui Xie; Zhiwei Zhang; Zhiqiang Liu; Jian Lan; Dake Chen; et al. (Science China Earth Sciences, 2019)

The effects of codon usage on the formation of secondary structures of nucleocapsid protein of peste des petits ruminants virus - Xiao-xia Ma; Yi-ning Wang; Xiao-an Cao; Xue-rui Li; Yong-sheng Liu; Jian-hua Zhou; Xue-peng Cai (Genes & Genomics, 2018)

Low-level concentrations of aminoglycoside antibiotics induce the aggregation of cyanobacteria - Lin-Rui Tan; Peng-Fei Xia; Raymond J. Zeng; Qian Li; Xue-Fei Sun; Shu-Guang Wang (Environmental Science and Pollution Research, 2018)

Repetitive transcranial magnetic stimulation inhibits Sirt1/MAO-A signaling in the prefrontal cortex in a rat model of depression and cortex-derived astrocytes - Zheng-wu Peng; Fen Xue; Cui-hong Zhou; Rui-guo Zhang; Ying Wang; Ling Liu; Han-fei Sang; Hua-ning Wang; Qing-rong Tan (Molecular and Cellular Biochemistry, 2018)

Phenylpropanoids from the fruits of Nicandra physaloides and their anti-inflammatory activities - Bing You Yang; Yan Liu; Hai Bing Jiang; Zhen Peng Xu; Rui Guo; Rui Wang; Xiao Mao Li; Hai Xue Kuang (Natural Product Research, 2017)

Genesis and tectonic setting of the Late Devonian Tawuerbieke gold deposit in the Tulasu ore cluster, western Tianshan, Xinjiang, China - Yi-Wei Peng; Xue-Xiang Gu; Peng-Rui Lv; Yong-Mei Zhang; Wen-Bin Cheng; Xin-Li Wang (International Geology Review, 2017)

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

Efficacy of Bt maize producing the Cry1Ac protein against two important pests of corn in China - Hong-Xing Chen; Rui Yang; Wang Yang; Liu Zhang; Ibrahima Camara; Xue-Hui Dong; Yi -Qing Liu; Wang-Peng Shi (Environmental Science and Pollution Research, 2016)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

Screening and test of CD40 related signal transduction pathway in AGS cells and construction of gene silencing vector - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue-Guang Zhang (Molecular Biology Reports, 2013)

Lack of association between IL-23R gene polymorphisms and systemic lupus erythematosus in a Chinese population - Gui-Mei Chen; Chen-Chen Feng; Qian-Ling Ye; Juan Wang; Han Cen; Rui Li; Hui Peng; Mo Zhou; Rui-Xue Leng; Yin-Guang Fan; Jin-Hui Tao; Hai-Feng Pan; et al. (Inflammation Research, 2013)

Effect of PI3K gene silencing on growth, migration and related proteins expression of CD40 signal-mediated gastric cancer cells - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue Guang Zhang (Molecular Biology Reports, 2013)

Paroxetine up-regulates neurogenesis in hippocampus-derived neural stem cell from fetal rats - Zheng-wu Peng; Fen Xue; Hua-ning Wang; Rui-guo Zhang; Yun-chun Chen; Ying Wang; Li-yi Zhang; Juan Fan; Qing-rong Tan (Molecular and Cellular Biochemistry, 2013)

Combined effect of sCD40L and PI3K siRNA on transplanted tumours growth and microenvironment in nude mice with gastric cancer - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue-Guang Zhang (Molecular Biology Reports, 2012)

CD40 signal expression in gastric cancer tissue and its correlation with prognosis of gastric cancer patients - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue Guang Zhang (Molecular Biology Reports, 2012)

Association of interleukin 23 receptor gene polymorphisms (rs10489629, rs7517847) with rheumatoid arthritis in European population: a meta-analysis - Yu Zhai; Ke Xu; Fen Huang; Hui Peng; Chen-Chen Feng; Kao-Kao Zhu; Rui-Xue Leng; Hai-Feng Pan; Dong-Qing Ye (Molecular Biology Reports, 2012)

Extraction of essential oils from garlic (Allium sativum) using ligarine as solvent and its immunity activity in gastric cancer rat - Rui Li; Wei-chang Chen; Wei-peng Wang; Wen-yan Tian; Xue-guang Zhang (Medicinal Chemistry Research, 2010)

Analysis of the essential oil of magnolia and its effect on antioxidant enzyme activity, sCD40L and phosphorylate-activate Akt protein levels in gastric cancer mice - Rui Li; Wei-chang Chen; Wei-peng Wang; Wen-yan Tian; Xue-guang Zhang (Medicinal Chemistry Research, 2010)